2018
DOI: 10.1364/oe.26.011292
|View full text |Cite
|
Sign up to set email alerts
|

Security of subcarrier wave quantum key distribution against the collective beam-splitting attack

Abstract: We consider a subcarrier wave quantum key distribution (QKD) system, where quantum encoding is carried out at weak sidebands generated around a coherent optical beam as a result of electro-optical phase modulation. We study security of two protocols, B92 and BB84, against one of the most powerful attacks for this class of systems, the collective beam-splitting attack. Our analysis includes the case of high modulation index, where the sidebands are essentially multimode. We demonstrate numerically and experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
1
43
0
2
Order By: Relevance
“…In order to achieve constructive interference, Bob should use ϕ 0 as an offset for his phase and apply microwave phase ϕ ϕ ϕ = + B 0 in his modulator. According to 36 , the average number of photons arriving at the first arm of Bob's detector in the transmission window T is…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve constructive interference, Bob should use ϕ 0 as an offset for his phase and apply microwave phase ϕ ϕ ϕ = + B 0 in his modulator. According to 36 , the average number of photons arriving at the first arm of Bob's detector in the transmission window T is…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, recent experiments 40 have shown that preservation of SCW quantum signal parameters in respect to the carrier allows transmitting phase-encoded quantum signals through the air providing invariance to telescope rotation that remains an important obstacle in traditional polarization-based free-space quantum communication, making the same QKD kit suitable for fiber and free-space QKD networks. Security proof of SCW QKD protocol with discrete variables against collective beam-splitting attack was proposed in 36 , and more recently general finite-key security proof was presented in 41 .…”
mentioning
confidence: 99%
“…The authors show the possibility of implementing a strong reference technique by monitoring the intensity of the carrier wave. A version of the BB84-like protocol with phase modulation has recently been demonstrated by several authors of this work in [7][8][9]18]. Proposed in the latter papers approach allows to decode only one state in each «basis» (the word basis only means two states with the phase difference ±π).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are point-to-point [1,2] and twin-field systems with three parties [3][4][5][6]. Further examples are systems based on phase modulated multi-frequency states known as subcarrier wave QKD (SCW QKD) [7,8]. In addition, the state preparation approach utilized in SCW QKD can also be applied to a twin-field QKD system [9].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is to investigate the vulnerability to the faked-state attack of another single-photon detector, ID Quantique ID210, which is currently commercially available [28] and has recently been used in several QKD setups [29][30][31]. Notably some of these experimental schemes are based on subcarrier-wave (SCW) QKD architecture where quantum states are formed at spectral sidebands of an intense light through phase modulation [32].…”
Section: Introductionmentioning
confidence: 99%